Legitimization in Phishing: A CDA Perspective - Tahereen, Tanzina (EAST WEST JOURNAL OF HUMANITIES, 2017)
This paper mainly aims at analyzing how various discursive strategies legitimizing different requests and assertions in phishing emails are exploited to exercise the social power abuse and influence cognitive knowledge of the users. This study attempts to interlock Van Leeuwen and Wodak’s (1999) four legitimization strategies and Van Dijk’s (1998, 2001, 2006) ‘triangulation approach’ of discourse-society-cognition cycle in order to analyze the legitimization strategies in phishing from a critical discourse perspective. The discursive approach includes the discursive strategies in legitimation, the social approach shows the social power abuse engaged in legitimization, and the cognitive approach presents the manipulation of the user’s beliefs influencing their actions. In order to conduct this study, qualitative method is applied in randomly selected 25 phishing emails as textual data.